Paisajes en un sector de la Quebrada de Humahuaca durante la Etapa Agroalfarera : Arqueología de Tumbaya (Jujuy, Argentina) - Scaro, Agustina (Access archaeology., 2020)
This is a landscape and ceramics study of Tumbaya located in Quebrada de Humahuaca (northern Argentina). The research aims to improve understanding of local pre-Inca societies and the impact of Inca domination on them from different lines of evidence.